Multiple noncritical phase-matchings in biaxial KTP crystal - Zadorozhnii, V.I.; Kornienko, M.E.; Sidenko, T.S. (Functional Materials, 2006)
А general approach is developed and conditions of noncritical phase matchings (РМ) of different multiplicity for the sum frequency generation process are analyzed taking a biaxial КТР crystal as an example. The approach is based on the consideration of general properties of a РМ surface constructed in the frequency and angle coordinates, analysis of their singular lines and intersection points of those lines. The lines of non-criticality in signal frequency or in the propagation angles of the interacting waves have been consid- ered on the РМ surface. The classification of double-uncritical (in frequency and one of the angles or in two angles) РМs is proposed. The possibility to realize a triple non-criti- cality in three independent quantities, for example, frequency and two angles, has been shown. It is found that the double non-criticality (in frequency and IR signal divergence) region can be scanned over the whole transparency range of КТР under frequency tuning of the long-wavelength laser pumping. Мultiple non-critical РМs allow visualizing the broadband IR spectra and IR images. На прикладi двовiсного кристала КTР розвинуто загальний пiдхiд i проведено аналiз умов некритичних фазових синхронiзмiв (ФС) рiзної кратностi для процесу генерацiї сумарної частоти. Пiдхiд заснований на розглядi загальних властивостей поверхнi ФС, побудованої у координатах частот i кутiв, та аналiзi особливих лiнiй i точок їхнього перетину. На поверхнi ФС розглянуто лiнiї некритичностi за частотою сигналу чи кутами поширення взаемодiючих хвиль. 3апропоновано класифiкацiю двократних некритичних ФС (за частотою й одном з кутiв чи за двома кутами). Показано можливiсть реалiзацiї трикратної некритичностi за трьома незалежними величинами, наприклад, частотою i двома кутами. Встановлено, що область двократної некритичностi за частотою та розбiжнiстю IЧ сигналу може скануватися вздовж всiєї областi прозоростi КТР при змiнi частоти довгохвильової лазерної накачки. Кратнi некритичнi ФС дозволяють вiзуалiзувати широкосмуговi IЧ спектри та IЧ зображення. На примере двухосного кристалла КTР развит общий подход и проведен анализ условий некритичных фазовых синхронизмов (ФС) различной кратности для процесса генерации суммарной частоты. Подход основан на рассмотрении общих свойств поверхности ФС, построенной в координатах частот и углов, анализе их особых линий, а также точек пересечения этих линий. На поверхности ФС рассмотрены линии некритичности по частоте сигнала или углам распространения взаимодействующих волн. Предложена классификация двукратных некритичных ФС (по частоте и одному из углов или по двум углам). Показана возможность реализации некритичности по трем независимым величинам, например, частоте и двум углам. Установлено, что область двукратной некритичности по частоте и расходимости ИК сигнала может сканироваться по всей области прозрачности КТР при перестройке частоты длинноволновой лазерной накачки. Кратные некритичные ФС позволяют визуализировать широкополосные ИК спектры и ИК изображения.